Market Competition in Transition Economies: A Literature Review - Klaus S. Friesenbichler; Michael Böheim; Daphne Channa Laster (Austrian Institute of Economic Research (WIFO), 2014)
This paper provides a survey of the effects of market competition in the transition economies of Eastern Europe and Central Asia. The pivotal element of the transition was inter-firm competition, which replaced economic planning as the method to identify demand. Pro-competitive policies that facilitated the transition are discussed, including international trade, attracting foreign direct investment and firm entry. Research topics with respect to competition changed as the transition advanced. The focus shifted from churn and macroeconomic shock-management in the initial phases toward firm entry, privatisation and restructuring of incumbents. In the later phases of transition, differentials in aggregate economic performance became obvious, pointing at institutional differences and their interplay with transitions. These are equally reflected by the degree of competition of the business environment. Also the methods changed with the evolution of the research agenda. Early case studies were displaced by large-scale, cross-country econometric studies as survey data became increasingly available.
Keywords: 330; competition; transition; survey; Eastern Europe and Central Asia